N-of-1 Trials for Assessing the Efficacy of Deep Brain Stimulation in Neuropathic Pain. - Green, A; Shad, A; Watson, R; Nandi, D; Yianni, J; Aziz, T (2004)
The objective of this study is to determine the usefulness of single-patient, randomised, controlled trials (N-of-1 trials) in assessing the efficacy of deep brain stimulation (DBS) in neuropathic pain. Seven patients with various causes of intractable neuropathic pain underwent insertion of deep brain stimulating electrodes into the periventricular gray area or ventroposterolateral nucleus of the thalamus. Preoperatively, pain was measured using Visual Analog Scales (VAS) and the McGill Pain Questionnaire (MPQ). At 6 months, these pain assessments were repeated. At this point all patients were entered into a N-of-1 trial with the DBS on and off. Data were analyzed using the Wilcoxon and Student t-tests. Following placement of the deep brain stimulator, VAS scores were significantly reduced in six of seven patients. McGill Pain Scores (MPS) showed pain reduction in four of seven. The results of the N-of-1 trials were most similar to the MPQ scores and showed that three of seven patients could accurately predict whether the DBS was on or off. In the N-of-1 trials, the time between changing the DBS from on to off (or vice versa) had an effect on the results and probably underestimated the efficacy. We conclude that N-of-1 trials are a useful tool for assessing DBS efficacy.